Cash to Digital Transformation: Policy Challenges and Opportunities in Improving Financial Inclusion - Dahliani, Klara Paskarena; Soesanto, Harry (Economic and Business Horizon, 2025)
The transition from cash-based payment systems to digital finance has emerged as a global phenomenon driven by advances in financial technology and a growing emphasis on financial inclusion. While this transformation offers significant opportunities to expand access to formal financial services, it also presents a number of policy challenges, particularly in developing countries with low levels of digital literacy. This study aims to explore the policy challenges and opportunities associated with the cash-to-digital transformation in enhancing financial inclusion. A qualitative research method with a literature study approach is used, analyzing academic publications, policy reports, and case studies from various countries. The research findings reveal that the success of this transformation depends on several important factors, including the readiness of digital infrastructure, public trust in the digital financial system, and the development of adaptive and inclusive regulations. The main contribution of this study lies in providing policy recommendations for governments, financial regulators, and fintech industry players in designing sustainable and inclusive digital transformation strategies. These findings are expected to serve as a foundation for policy makers to create a more effective digital financial ecosystem in promoting financial inclusion.